2020
DOI: 10.1038/s41598-020-77312-7
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of environmental indices in assessment of soil remediation with conventional and next generation washing agents

Abstract: Remediation of soils contaminated with metal must ensure high efficiency of metals removal, reduce bioavailability of residual metals and decrease ecological risk. Thus, for comprehensive environmental soil quality assessment, different indices must be used. In this study, suitability of 8 indices was used for soil highly contaminated with Cu (7874.5 mg kg−1), moderately with Pb (1414.3 mg kg−1) and low with Zn (566.1 mg kg−1), washed in batch and dynamic conditions with both conventional and next-generation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 45 publications
(46 reference statements)
0
11
0
Order By: Relevance
“…The advantage of using TA is that it decreases metal mobility (MF), defined as the ratio of the metal concentration in the F1 fraction to the sum of the metal concentrations in the F1, F2, F3, and F4 fractions [ 20 ]. Based on the MF, metal in soil can be considered immobile (<1%), weakly mobile (1–10%), moderately mobile (11–30%), highly mobile (31–50%), or very highly mobile (>50%) [ 7 ]. On the basis of this classification, metals in the unflushed soil were highly and very highly mobile.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The advantage of using TA is that it decreases metal mobility (MF), defined as the ratio of the metal concentration in the F1 fraction to the sum of the metal concentrations in the F1, F2, F3, and F4 fractions [ 20 ]. Based on the MF, metal in soil can be considered immobile (<1%), weakly mobile (1–10%), moderately mobile (11–30%), highly mobile (31–50%), or very highly mobile (>50%) [ 7 ]. On the basis of this classification, metals in the unflushed soil were highly and very highly mobile.…”
Section: Resultsmentioning
confidence: 99%
“…The distribution of the metals in the soil was determined using a modified BCR (Commission of the European Communities Bureau of Reference) procedure [ 31 ] in which metals were fractionated into four fractions using specific reagents: exchangeable and acid-soluble (mobile F1) extracted with 0.11 mol/L CH 3 COOH; reducible (potentially mobile F2) extracted with 0.5 mol/L NH 2 OH·HCl; oxidizable (potentially mobile F3) extracted with 1 mol/L CH 3 COONH 4 ; residual (immobile F4) extracted with HCl and HNO 3 mixed at a volume ratio of 3:1. Based on metal fractionation, the mobility factor (MF) was calculated [ 7 ] to compare metal mobility in soil before and after soil flushing. All physico-chemical analyses were performed in triplicate.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies on soil washing, the I r was a useful tool to evaluate metal-binding intensity in different matrices (soil, sludge), contaminated with different metals at different concentrations, washed under different conditions with various washing agents and with different effectiveness of metals removal [ 29 ]. Tang et al [ 51 ] demonstrated that after triple washing of sewage sludge with combined rhamnolipid and saponin, the stability of Cu increased from 0.23 to 0.47, and that of Pb from 0.25 to 0.55.…”
Section: Resultsmentioning
confidence: 99%
“…Metal stability in contaminated and washed soil, based on their chemical fractionation, was calculated according to Equation (2): where i is the index number of the BCR sequential extraction step, progressing from 1 (for F1 fraction) to 4 (for F4 fraction), k is the total number of fractions in the BCR procedure, F i is relative metal content in fraction i. The classification of metal stability based on the I r is as follows: lack of stability (I r ≤ 0.1), low stability (0.1 < I r ≤ 0.3), medium stability (0.3 < I r ≤ 0.5), elevated stability (0.5 < I r ≤ 0.7), high stability (0.7< I r ≤ 0.9) [ 29 ].…”
Section: Methodsmentioning
confidence: 99%